Plant succession in a denuded and plowed openfield ecosystem at the U.P. campus, Diliman, Quezon City - De Guzman, Rosalina Sarinas 1948- (1974)
This study followed the qualitative and quantitative measure of factors responsible for the ecological development of plants like other plants, animals and abiotic factors that influence its growth from the denuded field to the time it started to regenerate. The study took place at the UP Campus, Diliman, Quezon City.
Thesis (M.A.T.Biology)--University of the Philippines.
Keywords: Botany -- Ecology. -- Philippines; Plant succession